PEMILIHAN PAKET WEDDING MENGGUNAKAN METODE ELECTRE - Endah Sri Subrata; Susanti Margaretha Kuway; I Dewa Ayu Eka Yuliani (STMIK PONTIANAK, 2020)
Along with the development of technology that is increasingly rapidly and it cannot be denied that the technology as secondary to the needs of its users. So far this technology has also been applied to several fields, one example the presence of technology in the education sector which allows its users to do the wedding package selection process. This decision support system for determining criteria in addressing the issues facing a marriage in providing information that is timely, accurate and efficient for those who need the information, where the information contained in the data storage medium that is specially prepared. Research using ELECTRE method for calculation process and web-based applications with PHP programming language that can access each user regardless of where the user is based on the criteria of the results users can determine which criteria will be taken and according to the budget.